R̄ainḡan k̄anwǐchai r̄ưang k̄ansưks̄a khunnalaksana kh̨̄ong k̄anphr̄ærab̄at ȳas̄eptit ph̄ưa k̄anfao rawang nai sath̄an prak̨̄opk̄an khan̄at lek nai Prath̄et Thai = Drug abuse among workers in small scale industries in Thailand : a qualitative approach - Sirinan Kittisuksathit (Sath̄aban Wǐchai Prach̄ak̨̄on læ Sangkhom, Mah̄awitthaȳalai Mahidon, 2007)
Research on the spread of drug abuse among workers in small enterprises in Thailand.